The impact of board of directors diversity on earning forecast error in Malaysia IPO prospectus / Merely Kontuni - Kontuni, Merely (2016)
The current paper focuses on the factors that contribute to earnings forecast errors in Malaysian IPO prospectuses. Earning forecast in Malaysian IPO is used by investors to make investment decisions and to predict the future earnings of a company. The accuracy of the forecast is vital if the forecast is to be considered as a credible indicator. Therefore, errors in earning forecast are definitely something that investors should be concerned about Literature on forecast earnings determinants which are corporate governance characteristic proposed that corporate governance is related to earning management which in turn predicts forecast accuracy. In this case, corporate governance refers to the Board of director as the main factor that influences the accuracy of earnings forecast. The aim of this paper is (1) to determine the impact of ethnicity of the Board of Director on the earning forecast error in IPO prospectuses and (2) to determine the impact of gender of the Board of Director on the earning forecast error in IPO prospectuses. Regression analysis was carried out to discover the relationship between the variables in the study. To evaluate the earning forecast accuracy, the metric of Forecast Error (FER) was conducted. Data were collected from IPO prospectuses and annual reports of random companies which were listed in 2010 until 2015. The empirical results indicate that the Board of Director Diversity does not influence the earning forecast error.